30 - QUALITY OF LIFE IN ADULTS AFTER ENDOSKELETAL PROSTHESIS (Fiep Bulletin - online, 2011)
The term amputation is defined as the removal, usually by surgery, of all or part of a member. The lower-limb amputations are surgical procedures, in which they leave irreversible damage. The prostheses are tools used to replace any lost or malformed region of our body. The use of a prosthesis provides a normal body image, helping the individual to develop greater confidence and physical skills and improving their quality of life. Objective: To determine the quality of life of patients after receiving an endoskeletal prosthesis at Faculdade Assisi Gurgacz-F AG, Cascavel-PR. Methodology: This study is based on the application of SF -36 questionnaire for assessing the quality of life of patients in the pre-and post prosthetic fitting for the lower limbs. The population consisted of 30 subjects, 5 females and 25 males, average age between 30-70 years. As inclusion criteria, all patients had to have a lower limb amputation, and may be unilateral or bilateral and may already be using the endoskeletal prosthesis for at least three months. Results: Using the values (p = 0.05), one can that there has been improvement in quality of life after endoskeletal prosthesis in the areas: physical functioning, limitation, pain, health, vitality, social, emotional, mental health questionnaire adapted for the SF-36. Conclusion: One should not consider amputation as the end of something or simply the loss of a limb that eventually will generate disabilities, but consider it the beginning of a new phase, because if one side was the loss of a segment of life and a change in body image the other eliminated the danger of loss of life and gave relief to intolerable suffering, making it possible for greater freedom of action.
Keywords: Amputation; Quality of life; SF-36